Metallogenesis, hydrocarbons and tectonic patterns in Eastern Asia a program of research. - Committee for co-ordination of Joint Prospecting for Mineral Resources in Asian Offshore Areas (CCOP); Intergovernmental Oceonographic Commission, UNESCO (Bangkok Committee For Co-ordination of Joint Prospecting for Mineral Resources in Asian Offshore Areas (CCOP) and Intergovernmental Oceanographic Commision (IOC), UNESCO, 1974)
At head of title: International Decade of Ocean Exploration.Bibliography: p. 151-158
Report of the IDOE Workshop on Tectonic Patterns and Metallogenesis in East and Southeast Asia, Bangkok, Thailand, 24-29 September 1973
Keywords: Hydrocarbons; Ore deposits; Geology, Structural; Oceanography